2019
DOI: 10.1039/c8sm02301h
|View full text |Cite
|
Sign up to set email alerts
|

Destabilizing effect of perfluorodecanoic acid on simple membrane models

Abstract: The surfactant perfluorodecanoic acid (PFD), widely used in different industrial applications and an important environmental contaminant, can penetrate distearoyl phosphatidic acid (DSPA), dilauroyl phosphatidic acid (DLPA) and distearoyl phosphatidylethanolamine (DSPE) monolayers, even at high pressures values, above 30 mN m−1, which is the accepted lateral pressure value for a cellular bilayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…1,2 However, their specific properties, such as stability, has led to the persistence of PFAS in the environment (soil, water), as well as in wildlife and humans. 3,4,5,6,7,8 This raises environmental and human health concerns due to the toxicity and bioaccumulation of PFAS. Taking into account this hazard, it is important to monitor the presence and concentrations of PFAS.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, their specific properties, such as stability, has led to the persistence of PFAS in the environment (soil, water), as well as in wildlife and humans. 3,4,5,6,7,8 This raises environmental and human health concerns due to the toxicity and bioaccumulation of PFAS. Taking into account this hazard, it is important to monitor the presence and concentrations of PFAS.…”
Section: Introductionmentioning
confidence: 99%
“…This lipid is an essential component in the cell membrane’s ability to form membrane fusion structures (lipidmaps.org). PFOS has been shown to decrease multiple types of phospholipids in mouse kidney, including PAs and PEs [ 98 ], and this may be due to the degradation of the membrane protein components, resulting in membrane leakage and variation in rigid structure [ 99 , 100 , 101 ]. One recent study using injection of PFOS into zebrafish embryos at levels equal to and lower than those in this study found very similar results, with Yang et al [ 85 ] showing downregulation of PE and PCs in zebrafish embryos after PFOS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…36 We propose that anionic PFHA − is depleted from the protonated-DPPG interface because of repulsive interaction between their fluoroalkyl and alkyl chains. Surface tensiometry and Brewster angle microscopy 69 of anionic (distearoyl phosphatidic acid) lipid monolayer have also revealed that perfluoro decanoic acid is expelled from the anionic lipid monolayer interface at higher surface pressure (above 20 mN/m) but coexists with the lipid at lower surface pressure. In the following section, we have examined the headgroup-specific interaction of PFHA at zwitterionic DPPC/ water interface where anionic phosphate and cationic choline groups coexist at the interface.…”
Section: Ssmentioning
confidence: 99%